Pengaruh Ketinggian Permukaan Bahan Bakar di Dalam Mangkok Karburator Pada unjuk Kerja Motor Bensin - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
In Gas Engine, carburator use for regulate the mixing of gasoline and air (except engine with injection system). The fuel level in carburator fuel bowl will influence the engine performance. In this research, we will try to find the minimum fuel level in carburator fuel bowl (which still give enough a good engine performance). The fuel level in the carburator bowl can find through the glass wall of the fuel bowl itself The research start with the default level from manufacturer and then decreasing with 1 mm. In this research use NISSAN engine, 1597 cc, 4 cylinders with 80 PS at 5200 rpm. From the data, its shown that the trend of the economizing of fuel start at level â 5 mm from the default and maximum at level -7 mm. From the experience, the engine will difficult to start in the morning at this condition (minimum level of the fuel level in carburator bowl). This condition will different for another engine with different specification.